Examination of the Relationship between Stress and Sleep Quality Affecting Shooting Accuracy in Petanque Games - Ismail, Muhammad Ismail; Kamarudin, Kamarudin; Kandupi, Ardiansyah Dahlan (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. This study seeks to:1)determine if there is a relationship between sleep quality and shooting results in petanque games; 2) assess whether stress correlates with shooting results in petanque games. The findings of this study may serve as a valuable resource for coaches aiming to enhance the performance of petanque athletes, particularly in the area of shooting results improvement. Materials and Methods. This investigation is of a correlational nature. The participants in this study consisted solely of novice petanque players located in Central Sulawesi. A total of 31 individuals participated in the study. The instruments or methods for collecting data from the three variables include the Pittsburgh Sleep Quality Index questionnaire, a stress measurement questionnaire, and a petanque shooting test. The analysis employed in this study to examine the data is the partial correlation test. Results. The findings from the study indicate that the significance value for the relationship between sleep quality and shooting results in the petanque game is 0.892 ( > 0.05). This suggests that the alternative hypothesis in this study is accepted, while the null hypothesis is not accepted. This indicates that there is no correlation between sleep quality and shooting performance in the petanque game; 2) The significance value found for the relationship between stress variables and shooting performance variables in the petanque game is 0.934 ( > 0.05). This suggests that the alternative hypothesis in this study is accepted, while the null hypothesis is not accepted. This indicates that there is no correlation between stress levels and performance outcomes in petanque games. Conclusion. The findings of this study indicate the following: 1) No correlation exists between sleep quality and shooting performance in petanque; 2) No correlation exists between stress levels and shooting performance in petanque.